"Tourist' sense of place", an assessment of the sense of place in tourism studies: the case of Portugal - d'Orey, F.; Cardoso, A.; Abreu, R. (Academy of Strategic Management Journal, 2019)
The Sense of Place has been addressed in tourism studies as an object of concern to academics and policymakers. From mass tourism to personalized travel, understand the relationship between tourists and places it's an effort to improve the tourism sustainability. This article proposes to explore the perception of tourists in Portugal by modelling the Sense of Place dimensions. This approach introduces the holistic multidimensional concept of Sense of Place as a relationship between the tourists and the places they visit. Data from 500 surveys were subjected to Factor Analysis that confirmed four factors or dimensions of tourist's perception. This research has also found that some sociodemographic variables have a significant effect on tourist's Sense of Place. Tourism is a prominent subject area in marketing studies and this article brought to the discussion, a multivariate methodology to modelling individual perceptions of places. This method allowed us to identify a set of tourist profiles associated with these Sense of Place dimensions. Resulting in relevant outputs for the brand tourism management and destinations strategic planning.